Cultivation of Intrapreneurship: A Framework and Challenges - Huang, Lan-Ying; Yang Lin, Shu-Min; Hsieh, Ying-Jiun (Frontiers in Psychology, 2021)
Intrapreneurship has drawn research attention over the past decades considering its crucial role in innovation, organizational performance, and employee career planning. Intrapreneurial research based on various concepts also emerges. In spite of the increasing concern in the field, contributions in the field are fragmented. Particularly, intrapreneurship research is still lacking an integrated framework based on which, enablers and important facilitating mechanisms can be identified to enhance intrapreneurship. To close the above research gap, the study develops a holistic intrapreneurial framework. Specifically, the study first examines intrapreneurship in relation to other prominent concepts (i.e., innovation, entrepreneurship, and sustainability). This study then identifies enablers of intrapreneurship at both individual and organizational level. Notably, extant research largely examines intrapreneurship either at the organizational or individual level, and concentrates in corporate entrepreneurship or individual intrapreneurial employees. Research providing a holistic perspective on enablers for intrapreneurship is rare. The study further integrates these intrapreneurial enablers with facilitating mechanisms and proposes a framework of intrapreneurship. The framework makes it possible to clearly identify pivotal antecedents to intrapreneurship based on various theoretical lenses and analytical levels applied. Finally, the study addresses a list of managerial and technological challenges arising from the above framework and suggests future research agenda.